1983
DOI: 10.1016/0014-5793(83)81137-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholesterol on phosphate uptake by human red blood cells

Abstract: and keywords not received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This may suggest a role of cholesterol in AE1 stability and function. An increase in the level of cholesterol has been linked to a decrease in AE1 anion transport ( 87 , 88 , 89 ). This is probably due to an increase in the stiffness of the red blood cell plasma membrane, restricting the conformational change in AE1 associated with transport.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest a role of cholesterol in AE1 stability and function. An increase in the level of cholesterol has been linked to a decrease in AE1 anion transport ( 87 , 88 , 89 ). This is probably due to an increase in the stiffness of the red blood cell plasma membrane, restricting the conformational change in AE1 associated with transport.…”
Section: Discussionmentioning
confidence: 99%
“…A strong interaction of spin-labelled cholesterol with Band 3 has also been demonstrated [ 45 ]. Enriching cholesterol in red blood cells inhibits transport, while depleting cholesterol enhances transport [ 49 ]. Thus, cholesterol interaction with Band 3 modulates its transport activity, likely by rigidifying the dimer interface.…”
Section: Discussionmentioning
confidence: 99%
“…EPR measurements on ghost membranes indicated a strong interaction of spin-labelled cholesterol with Band 3 [ 45 ]. Enriched levels of cholesterol in erythrocytes deceased anion transport activity perhaps by restricting the conformational change in Band 3 that occurs during transport [ 49 ]. Band 3 interacts strongly with cholesterol and is proposed to contain a high affinity inhibitory cholesterol-binding site [ 44 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MD simulation studies have also suggested that there is enough space in the dimer interface for one phospholipid or sphingomyelin molecule. Cholesterol is known to inhibit anion transport and so may also play a regulatory role (Gregg and Reithmeier, 1983). Although Band 3 interacted with both 1-palmitoyl-2-oleoyl-phosphatidylserine (POPS) and phosphatidylinositol 4,5-bisphosphate (PIP 2 ) lipids, MD simulations have shown a strong preference for PIP 2 lipids.…”
Section: Band 3-lipid Interactionsmentioning
confidence: 99%